Electrochemical role of oxygen containing functional groups on activated carbon electrode - Tojo, Tomohiro; Sakurai, Kengo; Muramatsu, Hiroyuki; Hayashi, Takuya; Yang, Kap-Seung; Jung, Yong Chae; Yang, Cheol-Min; Endo, Morinobu; Kim, Yoong Ahm (ROYAL SOC CHEMISTRY, 2014)
We have experimentally and theoretically clarified the effect of oxygen functional groups on the capacitive performance of a photochemically treated activated carbon electrode. A high density of C=O groups at the mouth of the micropores, where the chemically active edge sites are predominantly available, increases the energy barrier for ions to enter the pores, thereby resulting in a large decrease in the specific capacitance.
Keywords: DOPED-GRAPHENE; RAMAN-SPECTROSCOPY; POROUS CARBON; ELECTROSORPTION CAPACITANCE; ENERGY; NANOTUBES; SUPERCAPACITORS; OXIDE; DYNAMICS; DENSITY